PENGARUH KEMAMPUAN APARATUR DESA TERHADAP PERENCANAAN PEMBANGUNAN DESA PANGU SATU KECAMATAN RATAHAN TIMUR KABUPATEN MINAHASA TENGGARA - KALIGIS, REIVANA; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2020)
Development aims to create a just and prosperous, and prosperous society. In the implementation of the development to be in accordance with the objectives set, the implementation is greatly supported by good management and organization. One of the management processes is planning. Without a plan, there is no basis for carrying out activities in development activities in the context of achieving goals. This study aims to determine the effect of the ability of the apparatus on village development planning Pangu Satu. This study uses quantitative research using the dimensions of technical, social and conceptual abilities for the capability variables and the dimensions of preparation, implementation and institutionalization for the planning variables for data collection techniques, namely questionnaires or questionnaires, observation and documentation. This research uses simple linear regression analysis. The results of this study are that the ability of the apparatus has a positive effect on village development planning. The conceptual ability of the government in development planning is in accordance with the procedure but the quality of the process is still not optimal, Cooperation and coordination of the village government with village officials are not going well. Keywords: Ability, Planning, Development